The Influence of Work Stress and Work Discipline on the Performance of Nosew Employees at PT Adis Dimension Footwear, Tangerang Regency - Destiyani, Ayu; Cahyono, Yoyok; Putra, Awang Darmawan (Faculty of Science and Technology University of Pramita Indonesia, 2025)
- The purpose of this study was to determine the extent of the influence of work stress and work discipline on the performance of employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method, namely research that describes variables as they are supported by data in the form of numbers generated from actual conditions. The population in this study were all employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency. The research sample consisted of 76 respondents. The technique used to determine the sample in this study was the simple random sampling technique.The results of this study indicate that (1) partially, work stress significantly affects the performance of employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (5.323> 1.993) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (2) Partially, work discipline significantly affects the performance of employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (5.585 > 1.993) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus Ha is accepted and H0 is rejected. (3) Simultaneously, work stress and work discipline significantly affect the performance of employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency, as indicated by Fcount > Ftable (108.524 > 3.12) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of work stress and work discipline, either partially or simultaneously, have a significant influence on the performance of employees in the Nosew section at PT Adis Dimension Footwear, Tangerang Regency.